Effect of thickness on optical properties of pure Epoxy Resin plates (Baghdad Science Journal, 2025)
In this study, Epoxy Resin plates was prepared by mixing epoxy(A) and hardner(B)with ratio(A:B) (3:1) with different thickness (0.3-0.96)cm. The effect of thickness on optical properties have been studied (absorption ,transmission ,reflectance) also the optical constant were found like (absorption coefficient, extenuation coefficient and refraction index) for all of the prepared plates.The results have shown that by increasing the thickness of plates., the absorption intensity increase in which at plates thickness (0.3-0.96)cm the absorption intensity were(1.54-1.43) respectively, and since absorption peak for epoxy occur in ultraviolet region and exactly at wavelength(368)nm and energy gap(Eg=3.05 eV) thus their good transmittance in the visible light regionThe plates have transmittance of about (60-83.4)% in visible region ,the refraction index for Elda epoxy is (n= 1.53 ) and its reflectance is (R=4 )% at wavelength (368 nm).